Detection of glucose variability in saline solutions from transmission and reflection measurements using V-band waveguides. (26th October 2015) - Cano-Garcia, Helena; Kosmas, Panagiotis; Sotiriou, Ioannis; Papadopoulos-Kelidis, Ioannis; Parini, Clive; Gouzouasis, Ioannis; Palikaras, George; Kallos, Efthymios
Abstract: This paper presents experimental results that demonstrate the correlation of glucose concentration in water and saline solutions with transmitted electromagnetic (EM) energy in the frequency range of 50–75 GHz. The system is based on placing the aqueous solutions in acrylic holding tanks sandwiched between two open V-band waveguides. The measured samples have clinically relevant range of glucose concentrations, as low as 0.025 wt%. Our measurements show for the first time that it is possible to establish an approximately linear relationship between the signals transmitted through this simple waveguide-based system and the glucose content in the samples. Accurate full-wave EM simulations confirm this linear correlation. The results suggest the possibility of developing a miniaturized non-invasive glucose sensing device based on the transmission of radio waves in this frequency range.